Математические методы современной теории тестирования - Ахламов, А. Г.; Белоус, Н. В.; Пархоменко, С. А.; Бекетова, Е. А. (УАДО, 2002)
The work considers the problem of knowledge estimation for remote education. This article considers the modem mathematical models, which destined for reliable examination of test results and takes reliable level of knowledge for students
Keywords: теория тестирования; дистанционное образование